'Lost in space': The role of social networking in university-based entrepreneurial learning. Issue 2 (April 2017) - Lockett, Nigel; Quesada-Pallarès, Carla; Williams-Middleton, Karen; Padilla-Meléndez, Antonio; Jack, Sarah
While entrepreneurship education increasingly uses various means to connect students to the 'real world', the impact of social networking on learning remains underexplored. This qualitative study of student entrepreneurs in the United Kingdom and Sweden shows that their entrepreneurial journey becomes increasingly complex, requiring skills and knowledge not solely developed through formal or non-formal learning. Social networks, and associated informal learning, are shown to be critical in developing social capital important to a student's entrepreneurial progress. This study exposes a key value of social networking and encourages educators to embed in the curriculum activities that facilitate informal learning.